Current Drug Treatment Strategies for Atrial Fibrillation and TASK-1 Inhibition as an Emerging Novel Therapy Option - Kraft, Manuel; Büscher, Antonius; Wiedmann, Felix; L’hoste, Yannick; Haefeli, Walter E.; Frey, Norbert; Katus, Hugo A.; Schmidt, Constanze (Frontiers in Pharmacology, 2021)
Atrial fibrillation (AF) is the most common sustained arrhythmia with a prevalence of up to 4 % and an upwards trend due to demographic changes. It is associated with an increase in mortality and stroke incidences. While stroke risk can be significantly reduced through anticoagulant therapy, adequate treatment of other AF related symptoms remains an unmet medical need in many cases. Two main treatment strategies are available: rate control that modulates ventricular heart rate and prevents tachymyopathy as well as rhythm control that aims to restore and sustain sinus rhythm (SR). Rate control can be achieved through drugs or ablation of the atrioventricular (AV) node, rendering the patient pacemaker-dependent. For rhythm control electrical cardioversion (eCV) and pharmacological cardioversion (pCV) can be used. While eCV requires fasting and sedation of the patient, antiarrhythmic drugs (AADs) have other limitations. Most AADs carry a risk for pro-arrhythmic effects and are contraindicated in patients with structural heart diseases. Furthermore, catheter ablation of pulmonary veins can be performed with its risk of intraprocedural complications and varying success. In recent years TASK-1 has been be introduced as a new target for AF therapy. Upregulation of TASK-1 in AF patients contributes to prolongation of the action potential duration (APD). In a porcine model of AF, TASK-1 inhibition by gene therapy or pharmacological compounds induced cardioversion to SR. The DOxapram Conversion TO Sinus rhythm (DOCTOS)-Trial will reveal whether doxapram, a potent TASK-1 inhibitor, can be used for acute cardioversion of persistent and paroxysmal AF in patients,potentially leading to a new treatment option for AF.